INCREASED ARACHIDONIC ACID-INDUCED THROMBOXANE GENERATION IMPAIRS SKELETAL MUSCLE ARTERIOLAR DILATION WITH GENETIC DYSLIPIDEMIA - Goodwill, Adam. G. (2008)
OBJECTIVE: To determine if arachidonic acid (AA)-induced skeletal muscle arteriolar dilation is altered with hypercholesterolemia in ApoE and LDLR gene deletion mice fed normal diet. This study also determined contributors to altered AA-induced dilation between dyslipidemic mice and controls; C57/Bl/6J (C57). METHODS: Gracilis muscle arterioles were isolated, with mechanical responses assessed following challenge with AA under control conditions and after elements of AA metabolism pathways were inhibited. Conduit arteries from each strain were used to assess AA-induced production of PGI(2) and TxA(2). RESULTS: Arterioles from ApoE and LDLR exhibited a blunted dilation to AA versus C57. While responses were cyclooxygenase-dependent in all strains, inhibition of thromboxane synthase or blockade of PGH(2)/TxA(2) receptors improved dilation in ApoE and LDLR only. AA-induced generation of PGI(2) was comparable across strains, although TxA(2) generation was increased in ApoE and LDLR. Arteriolar reactivity to PGI(2) and TxA(2) was comparable across strains. Treatment with TEMPOL improved dilation and reduced TxA(2) production with AA in ApoE and LDLR. CONCLUSIONS: These results suggest that AA-induced arteriolar dilation is constrained in ApoE and LDLR via an increased production of TxA(2). While partially due to elevated oxidant stress, additional mechanisms contribute which are independent of acute alterations in oxidant tone.